Study Living Qur'an Terhadap Tradisi Pembacaan Al-Quran di Kuburan Pagi dan Petang Selama Tujuh Hari - Novia Permata Sari; Risman Bustamam (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2021)
The habit of the people of Nagari Balimbing reading Yasin's letter in the morning and evening at the cemetery for seven days is a special attraction. The focus of the research is on the history of the emergence of the tradition of reading Yasin in the morning and evening at the cemetery for seven days, then the practice of reading Yasin in the morning and evening at the cemetery for seven days and the meaning of reading Yasin in the morning and evening at the cemetery for seven days. The type of research that the author uses is a type of field research or (field research) using qualitative descriptive methods. This research data collection technique was obtained from the results of observations, interviews and documentation of researchers with the results of the study it was known that this tradition had been going on from generation to generation which is still being carried out, which originated from the Tariqa Syatariyah brought by Sheikh Burhanuddin from Ulakan. The practice of this tradition is carried out in the morning and evening at the cemetery for seven days in a row by the family of the corpse, namely by reading alfatihah, watering talqin, reciting prayers for the torment of the grave, surah yasin, surah al-ikhlas, al-falaq and an-nas.